Consequences of increased temperature and acidification on bacterioplankton community composition during a mesocosm spring bloom in the Baltic Sea. Issue 2 (15th November 2012) - Lindh, Markus V.; Riemann, Lasse; Baltar, Federico; Romero‐Oliva, Claudia; Salomon, Paulo S.; Granéli, Edna; Pinhassi, Jarone
Summary Despite the paramount importance of bacteria for biogeochemical cycling of carbon and nutrients, little is known about the potential effects of climate change on these key organisms. The consequences of the projected climate change on bacterioplankton community dynamics were investigated in a Baltic Sea spring phytoplankton bloom mesocosm experiment by increasing temperature with 3°C and decreasing pH by approximately 0.4 units via CO2 addition in a factorial design. Temperature was the major driver of differences in community composition during the experiment, as shown by denaturing gradient gel electrophoresis (DGGE) of amplified 16S rRNA gene fragments. Several bacterial phylotypes belonging to Betaproteobacteria were predominant at 3°C but were replaced by members of the Bacteriodetes in the 6°C mesocosms. Acidification alone had a limited impact on phylogenetic composition, but when combined with increased temperature, resulted in the proliferation of specific microbial phylotypes. Our results suggest that although temperature is an important driver in structuring bacterioplankton composition, evaluation of the combined effects of temperature and acidification is necessary to fully understand consequences of climate change for marine bacterioplankton, their implications for future spring bloom dynamics, and their role in ecosystem functioning.